Induction of Apoptosis and Inhibition of Breast Cancer Cell Growth and Multicellular Tumor Spheroids by Paclitaxel Combined Curcumin-loaded PLA-TPGS-based Nanoparticles - Tu, Nguyen Dac; Anh, Tran Phan; Thu, Ha Phuong; Nam, Nguyen Hoai; Phuc, Nguyen Xuan; Nhung, Hoang Thi My (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 3, 2021)
Paclitaxel and curcumin have been reported as anti-cancer compounds. Here, we presented a novel combination of paclitaxel and curcumin-loaded PLA-TPGS (PTX-Cur/PLA-TPGS) nanoparticles prepared by a modified solvent extraction/evaporation technique. These nanoparticles were well distributed and stable in water. This combination of paclitaxel and curcumin gave a higher efficiency of both drugs in cytotoxicity, induced apoptosis, and effect on cell cycles of KPL4 cell line in comparison with the use of paclitaxel or curcumin alone or even a normal mixture of these two compounds. Furthermore, PTX-Cur/PLA-TPGS nanoparticles exhibited a powerful ability in preventing MCF7 spheroids growth. Interestingly, curcumin also functioned as both a drug and a label. Based on the autofluorescence of curcumin, the absorption of PTX-Cur/PLA-TPGS nanoparticles into MCF7 spheroids could be followed and calculated. These results suggest that the nanoparticle-combination may provide a promising multifunctional delivery system for anti-cancer drugs.